2022
DOI: 10.18502/jovr.v17i1.10175
|View full text |Cite
|
Sign up to set email alerts
|

Update on Management of Non-proliferative Diabetic Retinopathy without Diabetic Macular Edema; Is There a Paradigm Shift?

Abstract: Diabetic retinopathy (DR) is the major cause of visual impairment and blindness in the working-age population. Conventional management for nonproliferative diabetic retinopathy (NPDR) without diabetic macular edema (DME) is derived from the findings of the Early Treatment Diabetic Retinopathy Study (ETDRS). Although the ETDRS protocol basically includes observation, selected cases of severe NPDR may undergo scatter laser photocoagulation. Post-hoc analysis of recent trials has shown that patients with NPDR rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In the United States, the prevalence of DR is expected to double to over 15 million people by 2050, with similar trends predicted globally 4 . Premature vision loss associated with DR progression is the leading cause of visual impairment in working-age Americans, costing the United States ~$500 million annually in lost income 5,6 . Individuals with DR-associated visual impairment reported a lower vision-related quality of life than people without DR, including higher rates of mental distress and depressive symptoms 7 .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the United States, the prevalence of DR is expected to double to over 15 million people by 2050, with similar trends predicted globally 4 . Premature vision loss associated with DR progression is the leading cause of visual impairment in working-age Americans, costing the United States ~$500 million annually in lost income 5,6 . Individuals with DR-associated visual impairment reported a lower vision-related quality of life than people without DR, including higher rates of mental distress and depressive symptoms 7 .…”
Section: Introductionmentioning
confidence: 82%
“…4 Premature vision loss associated with DR progression is the leading cause of visual impairment in working-age Americans, costing the United States ~$500 million annually in lost income. 5,6 Individuals with DR-associated visual impairment reported a lower vision-related quality of life than people without DR, including higher rates of mental distress and depressive symptoms. 7 The increasing prevalence of DM puts millions more at risk for DR-associated vision loss, but per the American Diabetes Association (ADA), up to 95% of this vision loss is preventable with timely diagnosis and treatment of DR. 8 Laser photocoagulation and, more recently, intravitreal antivascular endothelial growth factor (anti-VEGF) injections are the current standards of care in the treatment of DR, but both are typically deferred until the retinopathy progresses to a high-risk proliferative stage when the visual prognosis is often poor.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated NPDR without DME management, and there is a debate between conventional management derived from the Early Treatment Diabetic Retinopathy Study (ETDRS), which included controlling the systemic conditions and observation, and anti-VEGF therapy. The PANORAMA and Protocol W randomized trials showed that an early intervention with aflibercept in moderately severe to severe NPDR significantly improved DR severity scale scores and reduced vision-threatening complications of DR [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions can result in progressive vision loss and, in severe cases, even blindness. With the global aging population, increased usage of electronic devices, and growing numbers of diabetic patients, the prevalence of DME is on the rise [1,2]. As the leading causes of irreversible vision loss worldwide, AMD and DME require reliable and accurate diagnostic and monitoring tools [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%